The molecular microbial ecology of sulfate reduction in the Rhodes BioSURE process - Chauke, Chesa Gift (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2002)
The research reported here investigated the use of a Baffle Reactor in order to study aspects of the biological sulfur cycle, where a floating sulfur biofilm formation occurs and where complex organic compounds provide electron donor sources. The development of a laboratory-scale Baffle Reactor model system satisfied the requirements for sulfate reducing bacterial biomass growth and sulfur biofilm formation. Since relatively little is known about the microbial ecology of floating sulfur biofilm systems, this study was undertaken to describe the sulfate reducing sludge population of the system together with its performance. A combination of culture- and molecular-based techniques were applied in this study in order to investigate the microbial ecology of the sulfate-reducing bacteria component of the system. These techniques enabled the identification and the analysis of the distribution of different sulfate reducing bacterial strains found within the sludge bioreactors. Strains isolated from the sludge were characterised based on culture appearance, gram staining and scanning electron microscopy morphology. Molecular methods based on the PCR-amplified 16S rRNA including denaturing gradient gel electrophoresis were employed in order to characterise sulfate-reducing bacteria within the reactors. Three novel Gram negative sulfate-reducing bacteria strains were isolated from the sludge population. Strains isolated were tentatively named Desulfomonas rhodensis, Desulfomonas makanaiensis, and Clostridium sulforhodensis. Results obtained from the Baffle Reactor showed that three dominant species were isolated from the DNA extracted from the whole bacterial population by peR. Three of these were similar to those mentioned above. The presence of these three novel unidentified species suggest that there are a range of other novel organisms involved in sulfate reduction processes.
Keywords: Water -- Purification -- Biological treatment; Acid mine drainage; Water -- Microbiology